2020
DOI: 10.1021/acs.jcim.0c00452
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Small-Molecule Calcium Sensitizers for Cardiac Troponin C: A Combined Virtual and Experimental Screening Approach

Abstract: Heart failure is a leading cause of death throughout the world and is triggered by a disruption of the cardiac contractile machinery. This machinery is regulated in a calcium-dependent manner by the protein complex troponin. Calcium binds to the N-terminal domain of cardiac troponin C (cNTnC) setting into motion the cascade of events leading to muscle contraction. Because of the severity and prevalence of heart failure, there is a strong need to develop small-molecule therapeutics designed to increase the calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…One of the current therapies 172 is to design small molecules that can stabilize an open structure of the TnC and facilitate binding of the TnC switch peptide. To identify potential small molecules for the treatment, Coldren et al 101 combined GaMD and high‐throughput virtual screening to predict binding conformations and affinities of small molecules in TnC. The simulations were compared with experiments for the TnC protein structures in complex with calcium sensitivity modulators.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the current therapies 172 is to design small molecules that can stabilize an open structure of the TnC and facilitate binding of the TnC switch peptide. To identify potential small molecules for the treatment, Coldren et al 101 combined GaMD and high‐throughput virtual screening to predict binding conformations and affinities of small molecules in TnC. The simulations were compared with experiments for the TnC protein structures in complex with calcium sensitivity modulators.…”
Section: Applicationsmentioning
confidence: 99%
“…In this review, we will present the principles and the most recent applications of GaMD. Robust GaMD has been established for advanced simulation studies of a wide range of biomolecular systems, especially the protein–nucleic acid interactions 63–65 such as the CRISPR (clustered regularly interspaced short palindromic repeats)–Cas9 gene‐editing system, 66,67 protein–protein/peptide interactions, 68–72 protein‐ligand binding, 55,56,73–76 protein folding, 77 protein enzymes, 52,58,78–92 membrane proteins (including GPCRs, 68,69,73,76,93–95 ion channels, 53,96 and γ‐secretase 97 ) and carbohydrates, 98–100 as well as drug design 101,102 …”
Section: Introductionmentioning
confidence: 99%
“…We have successfully demonstrated that knowledge of known actives significantly improves virtual screening. Previously, we had employed a similar strategy for a single target system, cardiac troponin with noteworthy success 63,64 . In this work, we verified the strength and generalizability of this approach over a diverse selection of target systems.…”
Section: Discussionmentioning
confidence: 99%
“…This observation emphasizes the importance of protein dynamics to its function, although the observed timescale in hydrogen-deuterium exchange experiments is quite different from those accessible with MD simulations. Second, the knowledge of the structural details can guide the development of Ca 2+ sensitizers and other troponin-binding compounds [19][20][21] for heart disease therapy. TnC, as well as TnC-TnI interfaces, are generally targeted by cardio-tonic drugs [22,23], and even the putative agent of the 'French paradox' -trans-resveratrol is also a TnC N-lobe targeting compound [24].…”
Section: Accepted Articlementioning
confidence: 99%